Use and Safety of Anthroposophic Medications for Acute Respiratory and Ear Infections: A Prospective Cohort Study - Harald J. Hamre; Anja Glockmann; Michael Fischer; David S. Riley; Erik Baars; Helmut Kiene (AboutScience Srl, 2007)
Objective Anthroposophic medications (AMED) are widely used, but safety data on AMED from large prospective studies are sparse. The objective of this analysis was to determine the frequency of adverse drug reactions (ADR) to AMED in outpatients using AMED for acute respiratory and ear infections. Methods A prospective four-week observational cohort study was conducted in 21 primary care practices in Europe and the U.S.A. The cohort comprised 715 consecutive outpatients aged ≥1 month, treated by anthroposophic physicians for acute otitis and respiratory infections. Physicians' prescription data and patient reports of adverse events were analyzed. Main outcome measures were use of AMED and ADR to AMED. Results Two patients had confirmed ADR to AMED: 1) swelling and redness at the injection site after subcutaneous injections of Prunus spinosa 5%, 2) sleeplessness after intake of Pneumodoron ® 2 liquid. These ADR lasted one and two days respectively; both subsided after dose reduction; none were unexpected; none were serious. The frequency of confirmed ADR to AMED was 0.61% (2/327) of all different AMED used, 0.28% (2/715) of patients, and 0.004% (3/73,443) of applications. Conclusion In this prospective study, anthroposophic medications used by primary care patients with acute respiratory or ear infections were well tolerated. Abbreviations A-: anthroposophy; ADR: adverse drug reactions; AE: adverse events; AM: anthroposophic medicine; AMED: AM medication; C-: conventional; ENE-patients: eligible, not enrolled patients; IIPCOS: International Primary Care Outcomes Study